Т.АМАНЖОЛОВТЫҢ «АСАЎ-БАРАҚ» ЖЫРЫНДАҒЫ ПАТРИОТЛЫҚ ИДЕЯ - Торткулбаева, Т.А.; Базарбаева, Г.; Ержанова, Н. (FAN va JAMIYAT, 2022)
The article deals with the historical theme in the work of the Kazakh poet T. Amanzholov, who lived in Karakalpakstan. The heroes of T. Amanzholov’s epic "Asau-Barak", patriotism and the struggle for peace in the epic are analyzed.